2004
DOI: 10.2174/1386207043328229
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Endotoxin Agents. 2. Pilot High-Throughput Screening for Novel Lipopolysaccharide-Recognizing Motifs in Small Molecules

Abstract: Lipopolysaccharides (LPS), otherwise termed 'endotoxins', are an integral part of the outer leaflet of the outer-membrane of Gram-negative bacteria. Lipopolysaccharides play a pivotal role in the pathogenesis of 'Septic Shock', a major cause of mortality in the critically ill patient, worldwide. The sequestration of circulatory endotoxin may be a viable therapeutic strategy for the prophylaxis and treatment of Gram-negative sepsis. We have earlier shown that the pharmacophore necessary for small molecules to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…2A), and (ii) additional, appropriately positioned hydrophobic group(s) are obligatory for the interaction to manifest in neutralization of endotoxicity. Leads obtained from high-throughput screening on focused libraries (4,44,45) and from molecular modeling studies and in silico docking studies (19) suggested that extension of the spermine backbone and the introduction of an additional, appropriately positioned amine on the scaffold would allow favorable salt bridges with the lipid A phosphate groups, analogous to that observed in complexes of lipid A and PMB (2), as well as additional H-bond interactions with the 3-deoxy-D-manno-octulosonic acid (KDO) sugars (30) in the inner-core region of LPS (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A), and (ii) additional, appropriately positioned hydrophobic group(s) are obligatory for the interaction to manifest in neutralization of endotoxicity. Leads obtained from high-throughput screening on focused libraries (4,44,45) and from molecular modeling studies and in silico docking studies (19) suggested that extension of the spermine backbone and the introduction of an additional, appropriately positioned amine on the scaffold would allow favorable salt bridges with the lipid A phosphate groups, analogous to that observed in complexes of lipid A and PMB (2), as well as additional H-bond interactions with the 3-deoxy-D-manno-octulosonic acid (KDO) sugars (30) in the inner-core region of LPS (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The BC displacement assay for quantifying binding affinity has been described previously (5,43,44). Briefly, to the first column (16 wells) of a Corning Nonbinding Surface 384-well flat-bottom black fluorescence microplate 80-l aliquots of 1 mM stock solutions of DS-96 or PMB (reference compound) were added in quadruplicate and were…”
Section: Methodsmentioning
confidence: 99%
“…Binding to the lipid A region of LPS was determined using the BODIPY-TR-cadaverine displacement assay (34,35), in which the probe bound to cell-free LPS is self-quenched but fluoresces when released in solution. Stock solutions of BODIPY-TRcadaverine (500 M) and LPS from P. aeruginosa (5 mg/ml) were prepared by dissolution in Tris buffer (50 mM, pH 7.4) (the Tris buffer was supplemented with 0.5% methanol for the former).…”
Section: Methodsmentioning
confidence: 99%
“…[15] Hence, there is a great deal of A C H T U N G T R E N N U N G interest in developing therapeutic agents that can efficiently bind LPS. [16] Third, whereas the therapeutic strategy directed against viral glycans was a success, a similar approach to antibacterial therapies has not been systematically explored due to difficulties in finding molecules that can selectively bind to bacterial glycans. [17] Herein, we report our findings in screening of 10 000 random 20-mer peptide sequences printed on a glass slide with newly developed luminescent LPS glycoprobes for potential lectinomimetic activity.…”
Section: Introductionmentioning
confidence: 99%